-6x-33=3x+12

Simple and best practice solution for -6x-33=3x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-33=3x+12 equation:


Simplifying
-6x + -33 = 3x + 12

Reorder the terms:
-33 + -6x = 3x + 12

Reorder the terms:
-33 + -6x = 12 + 3x

Solving
-33 + -6x = 12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-33 + -6x + -3x = 12 + 3x + -3x

Combine like terms: -6x + -3x = -9x
-33 + -9x = 12 + 3x + -3x

Combine like terms: 3x + -3x = 0
-33 + -9x = 12 + 0
-33 + -9x = 12

Add '33' to each side of the equation.
-33 + 33 + -9x = 12 + 33

Combine like terms: -33 + 33 = 0
0 + -9x = 12 + 33
-9x = 12 + 33

Combine like terms: 12 + 33 = 45
-9x = 45

Divide each side by '-9'.
x = -5

Simplifying
x = -5

See similar equations:

| 1.25x-n=2.5 | | -3=x+9?-2 | | -17-102= | | -27=-10t | | -4b+4b+16=7b-5b | | 0=-4x-36 | | x^2-1/10=0 | | 9-(-17)= | | -4(r+6)=-78 | | -5x-4=1 | | y+25=13 | | 4/6/2 | | 2x+4x=-7-17 | | 6=x/5 | | 3*1/10 | | 57=(2x-3)+4 | | S+0.1=0.21 | | 0.6g+11=50.6 | | 8/12/2 | | (x+3/3)=2-(x+1/8) | | 5.8-2.5= | | 50x-18+74x=10 | | X+x+3x+20=180 | | 8/12/5 | | 15+u-22=(-7)2 | | 4/6/10 | | 57=2x+1 | | 3x-2(x+1)=-7 | | 2(x)-9=1 | | 2(8n-5)+3=121 | | 3/5(10x-40)=20-4(x-1) | | 3x^2-48/2x^2+8x |

Equations solver categories